Effect of Remittance Inflow on Economic Growth of Nigeria - Owoeye, Taiwo; Omoniyi, Oluwatoyin Babatunde (Journal of Applied And Theoretical Social Sciences, 2024)
This study examined the effect of remittance inflow on economic growth of Nigeria. The study specifically analyzed the short run and long run of personal remittance inflow on annual growth rate of gross domestic product of Nigeria. The study focused on Nigeria over the period of 41 years spanning from 1981 to 2021.This study employed secondary time series data obtained from World development Index and Central Bank of Nigeria statistical bulletin. Data collated were analyzed by correlation analysis and unit root test, co-integration test, and Error correction model estimation. Result showed that on the short run remittance inflow exert insignificant negative effect on GDP growth of Nigeria (-0.337970, p > 0.05), while on the long remittance inflow exerts significant positive effect on GDP growth rate (1.973835, p < 0.05). This study established that inflow of personal remittance on the short run might be detrimental to the level of economic growth Nigeria if not channeled to productive engagement by recipients in the home country. Meanwhile on the long run, when the inflow rises consistently, the tendency to boost the level of economic growth is Nigeria is high and significant. Hence this study recommends the need for policies and programs as well as appropriate system reforms that encourage utilization of remittance for productive purposes. In addition there is need to put in place structure that will checkmate the rate of brain drain in the country, so as not to trade our quality human capital just for funds flow that might not necessarily be channeled equitably for productive activities in the short and intermediate term.